Delivery by Dendritic Mesoporous Silica Nanoparticles Enhances the Antimicrobial Activity of a Napsin‐Derived Peptide Against Intracellular Mycobacterium tuberculosis. Issue 14 (17th June 2021) - Beitzinger, Bastian; Gerbl, Fabian; Vomhof, Thomas; Schmid, Roman; Noschka, Reiner; Rodriguez, Armando; Wiese, Sebastian; Weidinger, Gilbert; Ständker, Ludger; Walther, Paul; Michaelis, Jens; Lindén, Mika; et al.
Abstract: Tuberculosis remains a serious global health problem causing 1.3 million deaths annually. The causative pathogen Mycobacterium tuberculosis ( Mtb ) has developed several mechanisms to evade the immune system and resistances to many conventional antibiotics, so that alternative treatment strategies are urgently needed. By isolation from bronchoalveolar lavage and peptide optimization, a new antimicrobial peptide named NapFab is discovered. While showing robust activity against extracellular Mtb, the activity of NapFab against intracellular bacteria is limited due to low intracellular availability. By loading NapFab onto dendritic mesoporous silica nanoparticles (DMSN) as a carrier system, cellular uptake, and consequently antimycobacterial activity against intracellular Mtb is significantly enhanced. Furthermore, using lattice light‐sheet fluorescence microscopy, it can be shown that the peptide is gradually released from the DMSN inside living macrophages over time. By electron microscopy and tomography, it is demonstrated that peptide loaded DMSN are stored in vesicular structures in proximity to mycobacterial phagosomes inside the cells, but the nanoparticles are typically not in direct contact with the bacteria. Based on the combination of functional and live‐cell imaging analyses, it is hypothesized that after being released from the DMSN NapFab is able to enter the bacterial phagosome and gain access to the bacilli. Abstract : The activity of the antimicrobial peptide NapFab against intracellular Mycobacterium tuberculosis ( Mtb ) is significantly increased by loading onto dendritic mesoporous silica nanoparticles (DMSN). This enhanced activity is based on a 30‐fold increased, DMSN‐mediated peptide uptake. Live‐cell fluorescence microscopy and electron microscopy reveal fast DMSN uptake in endosomal vesicles, intracellular degradation of the carrier, and a continuous peptide release.